PENGGUNAAN DIKSI PADA BERITA ONLINE DETIK.COM - Pitaloka Wibawani Puspa; Luluk Isani Kulup (Buana Bastra, 2018)
Language is of vital importance matter in human life. One of language function is to communicate. Along growth and advancement of technology, form of communication alsofollows expand and growing sophisticated. In other hand, can also getting the quickerinformation pass by internet that is from online news. Background this Research overshadows by existence of irrelevancy the usage of diction (word choice) that used by at onlinenews. As for research focus this is about diction (diction choice) at Detik.com online news?.Research Target this is describe the usage of diction (word choice) at Detik.com online news.By using descriptive research approach qualitative, this research takes data of have the shapeof phrase or sentence related to diction (word choice), whereas data source at research this isthe set of Detik.com online news. data collecting technique as used in research this is thedocumentation with steps collect online newses and then read citation from news referred as.At technique of data analysis, process of data of analysis have the shape of accurate dataobtained/got, classifying and coding data, interpret data, and conclude data. Base result ofdata analysis and discussion, can be concluded that existed some inaccurates in the usage ofdiction at Detik.com online news, that is at meaning connotative, synonym, antonym, publicword, special word, and foreign word.